Cardiac disease and pregnancy: a case series of 19 patients - El Ghali, El Hassan; Meziyane, Jihane; Aouragh, Soukaina; Taheri, Hafsa; Saadi, Hanane; Mimouni, Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
In industrialized countries, cardiac disease is a major cause of maternal mortality. The cardiac pathology is further made worse by the significant decrease in the heart function. Our work is a case series of 19 patients who have been admitted to the gynaecology-obstetrics department for the occurrence of pregnancy in the context of cardiac pathology. We report our results, along with a discussion and a review of literature. Cardiac disease is a major cause of maternal mortality in industrialized countries. Management of cardiac diseased pregnant women should be multidisciplinary.